Characterization of Pulmonary Vein Dimensions Using High-Definition 64-Slice Computed Tomography prior to Radiofrequency Catheter Ablation for Atrial Fibrillation - Catherine Gebhard; Nazmi Krasniqi; Barbara E. Stähli; Bernd Klaeser; Tobias A. Fuchs; Jelena R. Ghadri; Laurent Haegeli; Thomas F. Lüscher; Philipp A. Kaufmann; Firat Duru (Cardiology Research and Practice)
Background. Contrast-enhanced computed tomography is commonly acquired before radiofrequency catheter ablation (RFCA) for atrial fibrillation (AFib) to guide the procedure. We analyzed pulmonary vein (PV) ostial diameter and volumes on a high-definition 64-slice CT (HDCT) scanner in patients with AFib prior to RFCA. Methods and Results. This retrospective study included 50 patients (mean age 60.2 ± 11.4 years, 30 males) undergoing cardiac HDCT scanning before RFCA for drug refractory AFib and 50 age-, BMI-, and sex-matched controls with normal sinus rhythm undergoing HDCT. PV ostial diameter and volume were measured and calculated using a semiautomatic calliper tool. Total ostial PV volume was significantly increased in patients with AFib as compared to controls (P<0.005). Similarly, total ostial PV diameter was significantly increased in AFib compared to controls (P<0.001). In AFib, the largest PV volume and diameters were measured in right superior PV (P<0.05 versus controls). The difference in PV volume between patients and controls was most pronounced in right superior PVs (P=0.015). Right middle PVs were found more often in patients with AFib (16/50; 32%) than in normal subjects (7/50; 14%). Conclusion. Enlargement of PV ostial area and enlargement of volume are frequent findings in patients with drug refractory AFib. These parameters may add to the risk stratification for AFib recurrence following RFCA.